ULTRASOUND-GUIDED VACUUM-ASSISTED RESECTION: REPORT OF A CASE SERIES - Alves, Katyane Larissa; Rodrigues, Frank Lane Braga; Pinto, Sebastião Alves; Freitas-Junior, Ruffo (Mastology, 2026)
Objective: This study aims to report a series of cases of lesions that were probably benign (ACR® BI-RADS 3) and with a low degree of suspicion (ACR® BI-RADS 4A) submitted to vacuum-assisted resection for diagnostic and therapeutic purposes. Methods: From August 2020 to January 2022, 16 patients underwent ultrasound-guided 10-gauge vacuum-assisted needle resection under local anesthesia. The biopsy needle was positioned according to the echographic view of the lesion, in order to obtain the fragments by suction. After the procedure, a titanium clip was positioned demarcating the site. Results: We performed 16 vacuum-assisted resections in lesions whose largest diameter varied between 0.4 and 2.5 cm (median=1.4 cm and standard deviation (SD)=0.66). We obtained samples whose measurements of the set of fragments varied between 2.2 and 3.6 cm (median=3.0 cm and SD=0.37). Of the 16 cases, 15 histologies were benign, predominating fibroadenomas and having 2 complex sclerosing lesions. Only 1 ductal carcinoma in situ. We had 1 case of hematoma with clinical repercussions and 1 case of increased bleeding at the skin incision site, both managed conservatively with good evolution. Conclusion: In our case series, vacuum-assisted resection allowed the investigation and, in most cases, the necessary therapy for the management of BI-RADS 3 and BI-RADS 4A lesions when the histology was benign and provided sufficient diagnostic data for the conduction of the case of carcinoma in situ, in which the conservative surgery performed maintained the same histological diagnosis. Vacuum-assisted resection can, in selected cases, replace a diagnostic and/or therapeutic surgical procedure, reducing morbidity and costs in the investigation and treatment of breast lesions, with minimal complications.